Health insurance affects the use of disease-modifying therapy in multiple sclerosis. (26th July 2016) - Wang, Guoqiao; Marrie, Ruth Ann; Salter, Amber R.; Fox, Robert; Cofield, Stacey S.; Tyry, Tuula; Cutter, Gary R.
Abstract : Objective: To evaluate the association between health insurance coverage and disease-modifying therapy (DMT) use for multiple sclerosis (MS). Methods: In 2014, we surveyed participants in the North American Research Committee on MS registry regarding health insurance coverage. We investigated associations between negative insurance change and (1) the type of insurance, (2) DMT use, (3) use of free/discounted drug programs, and (4) insurance challenges using multivariable logistic regressions. Results: Of 6, 662 respondents included in the analysis, 6, 562 (98.5%) had health insurance, but 1, 472 (22.1%) reported negative insurance change compared with 12 months earlier. Respondents with private insurance were more likely to report negative insurance change than any other insurance. Among respondents not taking DMTs, 6.1% cited insurance/financial concerns as the sole reason. Of respondents taking DMTs, 24.7% partially or completely relied on support from free/discounted drug programs. Of respondents obtaining DMTs through insurance, 3.3% experienced initial insurance denial of DMT use, 2.3% encountered insurance denial of DMT switches, and 1.6% skipped or split doses because of increased copay. For respondents with relapsing-remitting MS, negative insurance change increased their odds of not taking DMTs (odds ratio [OR] 1.50; 1.16–1.93), using free/discounted drug programs for DMTs (OR 1.89; 1.40–2.57), and encountering insurance challenges (OR 2.48; 1.64–3.76). Conclusions: Insurance coverage affects DMT use for persons with MS, and use of free/discounted drug programs is substantial and makes economic analysis that ignores these supplements potentially inaccurate. The rising costs of drugs and changing insurance coverage adversely affect access to treatment for persons with MS.